Narratologie und Epistemologie Studien zu Goethes frühen Erzählungen - Meixner, Sebastian (Studien zur deutschen Literatur, 2019)
A narrative is more than story; it is a window into the world it narrates. Sebastian Meixner's book explores the juncture between narrative and world in his study of Goethe's early works. In three different constellations he investigates relationships of exchange between literature and science that Goethe used to ground the modern narrative.